Three new Batillipes species (Arthrotardigrada: Batillipedidae) from the brazilian coast - Santos, Erika (2017)
Three new tardigrade species, Batillipes brasiliensis sp. nov., Batillipes dandarae sp. nov. and Batillipes potiguarensis sp. nov., are described from shallow subtidal sediments of the Brazilian coast. B. brasiliensis sp. nov. and B. dandarae sp. nov. have toes 3 and 4 on leg IV different in length, so they can be included in the D group of species, while B. potiguarensis sp. nov., with toes 3 and 4 on leg IV equal in length belong to the A group. Batillipes brasiliensis sp. nov. is characterized by having an ala-like caudal expansion; cuticular projections on the coxal region of legs I-III, and lateral projections. The lateral projection located between the third and fourth legs is fringed with digit-shaped expansions. Batillipes dandarae sp. nov. has a dorsal blunt enlargement in the scapular region; a pointed triangular caudal appendage, and no lateral projections. The new species exhibits a sensorial spine on legs I inserted posteriorly and turning forward, and anus surrounded by a peculiar cuticular structure constituted by six platelets. Batillipes potiguarensis sp. nov. is characterized by a unique combination of characters: scapular region well developed, protruding laterally at the level of the first pair of legs; lateral blunt processes between legs, and prominent roundish caudal protrusion. In addition, the new species exhibits cephalic appendages with swollen tips, evident secondary clavae, and very short sense organs on the legs IV.